Respuesta de estudio de algunos componentes de una metodologia para investigar los cultivos asociados en el tropico latinoamericano - Flor Montoya, Carlos A.; Francis, C.A. (International Center for Tropical Agriculture, 1975)
Studies of planting dates, densities and patterns in maize bean associations were conducted in Colombia. An efficient methodology is needed to gain a better understanding of maize/bean systems and other crop combinations. The ideal system should minimize competition among the crops (for light, water and nutrients) and maximize complementation (e.g., by using maize as a support for beans). The studies suggest how the plant breeder might modify plants to enhance their productivity in multiple crop systems. A series of practices are also suggested for the farmer. Certain factors affecting the farmer are discussed, including diversity, human nutrition, risk, income distribution and efficient use of scarce resources for the small farmer. (AS)